Peran Kepala Sekolah dalam Mengelola Aksesibilitas Siswa di Daerah Padat Lalu Lintas di SMAN 01 Telukjambe Karawang - Chindy Shamantha; Shihab Solahudin; Srimuryati Srimuryati; Hinggil Permana (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2025)
Traffic congestion in the school area facing the campus is a serious problem that affects student mobility. This study analyzes the effect of traffic density on student mobility at SMAN 1 Telukjambe which is directly opposite Singaperbangsa University of Karawang. The research method used is descriptive approach with data collection through direct observation, interviews, and analysis of traffic policies that have been implemented in the area. The results show that the traffic density around the school and campus is influenced by the high volume of private vehicles, lack of efficient public transportation, and infrastructure conditions that do not optimally support student mobility. Other factors such as the presence of illegal parking, low awareness of road users in obeying traffic rules, and lack of supervision of traffic policy implementation also contribute to the congestion. Various policies have been implemented, including traffic engineering, provision of school safety zones, and parking management, but their effectiveness is still limited due to a lack of coordination between related parties. Therefore, more comprehensive solutions are needed, such as improved public transportation, infrastructure improvements for pedestrians and cyclists, and stricter law enforcement against traffic violations. With integrated efforts, it is expected that student mobility can increase so that educational activities at SMAN 1 Telukjambe can run more smoothly and safely.